Opportunities And Challenges In Publishing And Promoting Scientific Journals In Bulgaria - Kiril Dimitrov (Journal of Management Sciences and Applications, 2022)
Presentation of scientific papers is associated with the creation of new scientific journals and the maintenance of established periodicals. This paper discusses and analyzes two challenges to publishing scientific journals in Bulgaria -first, securing a pool of suitable reviewers and second -maintaining good relations with potential authors. The paper proposes views based on exponential thinking that would lead to profound, positive changes based on the use of new technologies in scientific journal publishing. In practice, they are inextricably linked to the implementation of social innovations, resulting from the establishment of a new balance among stakeholders at different levels of realization of management. The paper attempts to assist lecturers and researchers in their professional pursuits.
Keywords: M12; M14; I20; 650; organizational culture; educational and research institutions; human resource management; exponential thinking